2016
DOI: 10.4103/0972-124x.188335
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge preservation using autogenous tooth graft versus beta-tricalcium phosphate alloplast: A randomized, controlled, prospective, clinical pilot study

Abstract: Background:A randomized, prospective clinical, radiographical, and histological study was conducted to evaluate healing after alveolar ridge preservation technique using two different graft materials, namely, a novel autogenous graft material i. e., autogenous tooth graft (ATG) and beta-tricalcium phosphate (β-TCP) alloplast.Materials and Methods:Fifteen patients undergoing extraction of at least three teeth were selected. Atraumatic extractions were performed. Of the three extraction sockets, one was grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 19 publications
2
59
0
2
Order By: Relevance
“…The radiographic density was included as the primary outcome as it can indirectly be correlated to anatomical and histological bone quality which is advantageous for successful dental implant (Silva et al, 2012, Huang et al, 2014, Almasoud et al, 2016. The value of Hu at the ADD group in our study came in accordance with the results of the study by Jun et al 2014 The autogenous graft from teeth was compared to β-tricalcium phosphate (TCP) for socket preservation in a split-mouth randomized trial including 15 patients (Joshi et al, 2016); the bone graft derived from teeth exhibited better dimensional preservation than the alloplasts after 4 months which was statistically significant. The graft derived from teeth was also compared to deproteinized bovine bone mineral (DBBM) xenograft for their effect in halting bone resorption and for the implant rehabilitation by Pang et al (2017) and both materials were equally effective for preserving the ridge height and width as well as for implant stability afterward with no statistically significant difference.…”
Section: Discussionsupporting
confidence: 69%
“…The radiographic density was included as the primary outcome as it can indirectly be correlated to anatomical and histological bone quality which is advantageous for successful dental implant (Silva et al, 2012, Huang et al, 2014, Almasoud et al, 2016. The value of Hu at the ADD group in our study came in accordance with the results of the study by Jun et al 2014 The autogenous graft from teeth was compared to β-tricalcium phosphate (TCP) for socket preservation in a split-mouth randomized trial including 15 patients (Joshi et al, 2016); the bone graft derived from teeth exhibited better dimensional preservation than the alloplasts after 4 months which was statistically significant. The graft derived from teeth was also compared to deproteinized bovine bone mineral (DBBM) xenograft for their effect in halting bone resorption and for the implant rehabilitation by Pang et al (2017) and both materials were equally effective for preserving the ridge height and width as well as for implant stability afterward with no statistically significant difference.…”
Section: Discussionsupporting
confidence: 69%
“…1 Tooth-derived demineralized dentin matrix (DDM) was first introduced in 1967, and several studies have shown that DDM has a chemical composition similar to bone. [2][3][4][5] Due to chemotactic properties for osteoblasts and osteoprogenitor cells, DDM from the patient's own extracted healthy tooth can be used for promoting the bone regeneration process at reconstructive dentistry, including extraction socket preservation, ridge augmentation, sinus bone graft, and guided bone regeneration (GBR) for implant site development. [6][7][8] There continues to be controversy regarding the medical choice of retention and removal of severely loose teeth due to periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have some essential drawbacks including donor site morbidity, limited availability, and additional payment . Tooth‐derived demineralized dentin matrix (DDM) was first introduced in 1967, and several studies have shown that DDM has a chemical composition similar to bone . Due to chemotactic properties for osteoblasts and osteoprogenitor cells, DDM from the patient's own extracted healthy tooth can be used for promoting the bone regeneration process at reconstructive dentistry, including extraction socket preservation, ridge augmentation, sinus bone graft, and guided bone regeneration (GBR) for implant site development …”
Section: Introductionmentioning
confidence: 99%
“…[11] Since then, a number of studies have shown promising results using dentin in comparison to various commercially available bone graft substitutes. [12131415] This is possibly due to the fact that bone and dentin possess similar biochemical properties. Dentin has shown to contain BMPs, insulin-like growth factor (IGF)-II, vascular endothelial growth factor, and transforming growth factor (TGF)-β. Cementum, a bone-like material surrounding tooth roots, also contains TGF-β, IGF-I, and type I and type III collagen, possibly contributing to its osteoinductive potential.…”
Section: Discussionmentioning
confidence: 99%